2013
DOI: 10.1111/ced.12044
|View full text |Cite
|
Sign up to set email alerts
|

A prospective case series of secondary intention healing for surgical wounds on the dorsum of the hand

Abstract: Secondary intention healing of surgical wounds on the dorsum of the hand is a useful management option, which is well tolerated by patients, has a low rate of complications, and gives good cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The use of topical steroids for hypergranulation has been reported in the non-burn literature to reduce granulation tissue, decrease pain, and accelerate reepithelialisation. 2 , 23 , 24 Concordantly, this review found some evidence that steroids are successfully used to treat inflammation and hypergranulation in burns, with all studies reporting improvements in timely reepithelialisation and regression of granulation tissue. On the other hand, topical steroids are historically equated with a reduction in the body's capability to heal wounds.…”
Section: Discussionmentioning
confidence: 77%
“…The use of topical steroids for hypergranulation has been reported in the non-burn literature to reduce granulation tissue, decrease pain, and accelerate reepithelialisation. 2 , 23 , 24 Concordantly, this review found some evidence that steroids are successfully used to treat inflammation and hypergranulation in burns, with all studies reporting improvements in timely reepithelialisation and regression of granulation tissue. On the other hand, topical steroids are historically equated with a reduction in the body's capability to heal wounds.…”
Section: Discussionmentioning
confidence: 77%
“…Broadly speaking, reconstructive options for medium to large dorsal hand defects include healing by secondary intention, purse-string closure, linear repair, full or split-thickness grafts, advancement flaps, rotation flaps, and transposition flaps [ 5 ]. Healing by secondary intent is typically not an ideal option for larger defects on the dorsal hand due to long healing times, scar contraction, and poor cosmetic results [ 9 ]. Purse-string closures help reduce the size of a large wound but can result in excessively high tension on fragile thin skin, and circumferential pleating [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healing by secondary intent is typically not an ideal option for larger defects on the dorsal hand due to long healing times, scar contraction, and poor cosmetic results [ 9 ]. Purse-string closures help reduce the size of a large wound but can result in excessively high tension on fragile thin skin, and circumferential pleating [ 9 , 10 ]. Linear repairs are also difficult due to high tension and potentially compromised articulation of the digits and wrist in the short postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,10 The use of SIH has expanded to include anatomic areas that notably lack features associated with superior SIH results. Favorable outcomes have been demonstrated from SIH in MMS defects in the nose, 3,10 forehead and scalp, 11,12 lips, [13][14][15] pretibial surface, 8 hand/finger dorsum, 16,17 lower eyelids, 18 and helix. 19 In accordance, this study demonstrates good SIH results in both traditional (concave, superficial, and/or small) and nontraditional (convex, deep, and/or large) wounds.…”
Section: Discussionmentioning
confidence: 99%